Study of some of the mechanisms involved in the prevention against Salmonella enteritidis serovar Typhimurium infection by lactic acid bacteria - Gobbato, Nadia Margarita (2008)
The possible mechanism exerted by different lactic acid bacteria (LAB) in the protection against Salmonella enteritidis serovar Typhimurium (S. typhimurium) infection was determined. LAB was administered to BALB/c mice, and the animals were subsequently challenged with S. typhimurium. The inhibition of the translocation of S. typhimurium in the liver was correlated with a decrease in cellular apoptosis determined in slices from the small intestine of mice. The microbiocidal activity of peritoneal macrophages was increased by Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus thermophilus, but not for the probiotic strain L. casei CRL 431. The levels of IFNγ and Bcl-2 positive cells in the small intestine of mice fed with the LAB were also determined by immunofluorescence. Using in vivo studies, we demonstrated that the biological and immune mechanisms induced by the LAB studied were different for each bacterium and were mediated by anti-S. typhimurium S-IgA microbiocidal activity and/or cellular apoptosis inhibition of infected immune cells.